The effect of using social media programs to obtain history material Among literary fifth graders Raed Kassad Azeez AL Yasir education of Karbala - Zghair Nadheer AL-Khafaji, Mohammed (International Journal of Psychosocial Rehabilitation, 2020)
This research aims to know: (The effect of using social networking programs to obtain history subject for literary fifth graders) To achieve the research goal, the following zero hypothesis was developed: (There is no statistically significant difference between the average score of the students of the experimental group who are studying history subject using social media programs and the average of the achievement levels of the control group who study in the traditional way). The research was limited to students of the fifth literary class in the holy province of Karbala and teaching the subjects of the first three chapters of the book Modern and Contemporary History of Europe and America for the fifth literary class scheduled for teaching for the academic year 2019-2020 in Iraq. The researchers prepared an objective test consisting of (25) paragraphs of multiple choice as a research tool after verifying their validity and reliability, and the researchers used a set of statistical means (Pearson correlation coefficient, Kay square, T-test, coefficient of difficulty, ease and distinction). The research found that the experimental group that studied modern and contemporary history of Europe and America in social networking programs surpassed the control group who were studying in the traditional way.